The Swiss UMTS Spectrum Auction Flop: Bad Luck or Bad Design - Elmar G. Wolfstetter (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper gives an account of events, and explains some systematic reasons of the UMTS auction flop in Switzerland. Apart from general market developments, which could not have been anticipated, we argue that auctiondesign which was introduced in England and adopted in Switzerland and elsewhere is a cause of the disappointing performance of many UMTS auctions in Europe, of which Switzerland is just one particularly pronounced example. The regulator would have been better advised to import some keyingredients of the auction design employed in Germany and Austria. This would have assured higher revenue or more competition. The paper closes with several proposals on how one should conduct future spectrum auctions.
Keywords: 330; spectrum auctions; telecommunications; industrial organization